A melancolia do progresso: o elo alegórico sobre a modernidade em Os condenados de Oswald de Andrade - Maio, Sandro Roberto (2008)
The Essay develops a reflection on the first modernist speech from the figure of the poet-author. It rethinks the role of the workmanship, considered lesser for critics, in the passage from pre modernism and in the poetic of Oswald de Andrade. The theoretical key is the way Walter Benjamin s reading understands Baudelaire, which makes possible the characterization of two central figures in the modern imaginary: the poet-symbol and the poet-allegory. From this point it delineates a central question of this research: What measured, in the Trilogy, the allegorical link on the images of modernity aims a speech of rupture of the symbolic projection of -bourgeois standards of representation. The hypothesis of replying this questioning is what the narrative constructs as style of Baudelaire reading fiction to, by means of allegory put in crisis the representation. When denying the normative speech by means of double, it becomes fictional product of readings and, therefore, it is cited text, fiction of a modernity reading. The Benjamin s concepts of allegory and symbol, in connection with the function of the poet in modernity, had been determinative for the development of the critical reflection on the Trilogy. The analysis methodology will make the approach between the corpus and theoretical fundamental by means of the allegorical key, what makes viable the correspondence between reading and fiction in the constructive process of the Trilogy. The romance ruptures with the analytical linearity of the tradition when incorporating a poetical narrative skipping, in order to materialize the wandering look, used to flanerie, the cheat poet. As conclusion, it highlights the bogus epic of the Trilogy, what transforms the poet in hero, approaching him to the prostitute eyes: to gaze intently the poetic prey to deduce the singular in the middle of merchandise standardization. The Trilogy of the Exile is affirmed, then, as a writing that transits not for symbols, but between symbols, in order to inscribe in its body a decomposed universality. The narrative voice, projects in the other convicted voices splinters of someone disfigured, translated, in the plan of the enunciation, as an experience of disintegration of the aura by means of the experience of the shock